Bibliography on Philippine medicinal plants - Bautista, Luviminda B.; Dimalanta, Clarisa G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1981)
This study presents a systematic compilation of information on Philippine medicinal plants. The compilation, which includes information materials dating back to Spanish times up to 1978, has been undertaken for the following reasons: 1) to help meet the growing demand for a unified bibliography on Philippine medicinal plants, and 2) to insure some adequate means of bibliographic control over the mass of materials on Philippine medicinal plants that have accumulated over the years.
The compilation brings together a total of 336 publications, reports, studies, researches, and other materials on Philippine medicinal plants. Annotations/abstracts are provided for each to be more relevant and valuable to users.
The normative survey type of descriptive research was employed in the gathering of materials from the different scientific and medical libraries visited. Bibliographical catalogs, literature listings, and bibliographies appended to individual works were used and consulted in searching for the various items to be included in the compilation. Author-title and subject indexes are provided to facilitate the location of entries.
It is hoped that this bibliography will serve as a research and information tool to facilitate efforts of researchers and investigators in the conduct of their scientific studies on medicinal plants, and that it will encourage a growing interest in the use of herbal medicine.
Mimeographed.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Botany, Medical--Philippines--Bibliography.; Medicinal plants--Philippines--Bibliography.; Plants, Medicinal See Medicinal plants